2013
DOI: 10.1159/000351422
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aspirin on Release of Eoxin C4, Leukotriene C4 and 15-HETE, in Eosinophilic Granulocytes Isolated from Patients with Asthma

Abstract: Background: The effect of aspirin on the release of key arachidonic acid metabolites in activated eosinophils from subjects with aspirin-intolerant asthma (AIA) has not been investigated previously, despite the characteristic eosinophilia in AIA. Methods: Peripheral blood eosinophils were isolated from four groups of subjects: healthy volunteers (HV; n = 8), mild asthma (MA; n = 8), severe asthma (SA; n = 9) and AIA (n = 7). In the absence or presence of lysine-aspirin, eosinophils were stimulated with arachid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Based on the data presented here by James et al [9], it appears that the 15-LO pathway is a potential therapeutic target for AIA and severe aspirin-tolerant asthma. Based on the known biological effects of 15-HETE, it is reasonable to hypothesize that inhibition of 15-LO may reduce inflammatory cell influx and hence lead to improved control in more severe asthma.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Based on the data presented here by James et al [9], it appears that the 15-LO pathway is a potential therapeutic target for AIA and severe aspirin-tolerant asthma. Based on the known biological effects of 15-HETE, it is reasonable to hypothesize that inhibition of 15-LO may reduce inflammatory cell influx and hence lead to improved control in more severe asthma.…”
mentioning
confidence: 61%
“…It has been shown that 15-HETE production in the peripheral blood leukocytes from aspirin-intolerant asthmatics is different from that in aspirin-tolerant asthmatics [8]. The study presented by James et al [9] further refines this study by isolating eosinophils from the peripheral blood leukocytes and identifying differences in patients with AIA. It has also been shown that the 15-HETE released from nasal polyps obtained from aspirin-sensitive individuals does not cause activation of eosinophils and/or mast cells [10].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…There is also a relative increased PGD 2 production (a Th2/ eosinophil chemoattractant) [113]. Additionally, activated eosinophils from AERD patients produce significantly higher amounts of leukotriene C 4 than eosinophils from healthy subjects or mild asthmatics [114]. This may also reflect the overactivity of the 5-LOX pathways in these subjects, that is exaggerated by the administration of aspirin.…”
Section: Aspirin-exacerbated Respiratory Diseasementioning
confidence: 99%
“…11 Recently, it was reported that 15-LOX-1 activity was greater in eosinophils derived from patients with severe asthma or aspirin-intolerant asthma (AIA) compared to eosinophils isolated from patients with mild asthma or healthy controls. 12 There are numerous publications regarding 15-LOX-1 inhibitors, but many studies are conducted using 15-LOX-1 from nonhuman species, most notably soybean (see, e.g., Refs. [13][14][15].…”
Section: Introductionmentioning
confidence: 99%